Time Controlled Speed Strength Method (TCSSM) to Increase the Explosive Power of Arm and Leg Muscles of Jiu-jitsu Athletes in Magetan Regency: An Implementation of a Strength Training Program - Sabitha Early Rasendriya, Tutur Jatmiko, Muhammad Kharis Fajar, Nafisa Arif Pambudi, Farjana Akter B (Lembaga Bale Literasi, 2025)
Explosive muscle power is a fundamental physical component that supports the execution of technical movements in Brazilian Jiu-Jitsu, particularly in actions such as takedowns, sweeps, and guard passes that require rapid and powerful force generation. Nevertheless, many training programs implemented at the regional level remain general and have not yet applied specific strength training methods aimed at developing speed–strength capacity. Therefore, this study aimed to evaluate the effectiveness of the Time Controlled Speed Strength Method (TCSSM) in enhancing the explosive power of the arm and leg muscles of Brazilian Jiu-Jitsu athletes in Magetan Regency. This research applied a quasi-experimental design with a one-group pretest–posttest approach involving 15 athletes aged between 15 and 23 years who had a minimum of three years of training experience. Participants completed a TCSSM-based strength training program for six weeks with a frequency of three sessions per week. The explosive power of the upper limbs was assessed using the Medicine Ball Throw (MBT) test, while lower limb explosive power was measured using the Vertical Jump (VJ) test. Data were analyzed through descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-test with a significance level of 0.05. The findings revealed a significant improvement in both variables following the training intervention. The mean MBT score increased from 5.39 m in the pretest to 5.99 m in the posttest, while the mean VJ score improved from 0.62 m to 0.68 m. Statistical testing confirmed significant differences between pretest and posttest scores for MBT (t = -7.937; p < 0.05) and VJ (t = -6.159; p < 0.05). These results indicate that the TCSSM-based training program effectively improves the explosive power of both arm and leg muscles in Brazilian Jiu-Jitsu athletes. Accordingly, TCSSM can be considered an effective and applicable strength training method to support the physical performance development of grappling athletes.